3y+6=-x

Simple and best practice solution for 3y+6=-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+6=-x equation:


Simplifying
3y + 6 = -1x

Reorder the terms:
6 + 3y = -1x

Solving
6 + 3y = -1x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3y = -6 + -1x

Combine like terms: 6 + -6 = 0
0 + 3y = -6 + -1x
3y = -6 + -1x

Divide each side by '3'.
y = -2 + -0.3333333333x

Simplifying
y = -2 + -0.3333333333x

See similar equations:

| -4x-2(3x-10)=80 | | -2x+3=-2(x+3) | | -2x+5(-3x+26)=-57 | | 3x^2+4x-7=13 | | 5x+8y-3=0 | | (8n^2-n+5)(4n^2+2n+2)= | | 3x+4(-4x-27)=35 | | 3-2x=5+3x | | -5p+8=2(3p-2)-3(-8+5p) | | 7-x=-8-x | | -6=n-210 | | 5n+10n=6.35 | | T-42=3 | | 1/2(x+6)=3/2x-1 | | 14+7(x-9)=28 | | 4y+12=-3x | | -(m+6n-13)= | | 2r=1.33r+8 | | (2n^2+5n+8)(2n^2-6n-1)= | | 15+10p-8=p+9p+13 | | -19th+12=-14th-8 | | -5x-7(-2x+3)=-66 | | 3+2.7x=4.7 | | 3(2x-5)=5(x-4)1x+5 | | 3z=-7+17 | | 8k-4.7=3k+0.4 | | 28=-48 | | F(x)=2w^2-5w-14 | | 3x(5x-5)= | | 1.5(5-x)=.25 | | -2.3q+16=-50-38 | | v=x(24-2x)(16-2x) |

Equations solver categories